Optimization of Concentration and Staining Duration of Methyl Green in The Examination of Escherichia coli DNA Bands Using Agarose Gel Electrophoresis - Adrian Prasetya, Rifky; Merdekawati, Fusvita; Iin Nur Indra, Asep; Djuminar, Ai (LPPM STIKes Muhammadiyah Ciamis, 2024)
Background & Objective: Nowadays, many alternative dyes are used for staining DNA during electrophoresis, one of which is Methyl Green. Methyl Green has several advantages, including being cheaper than EtBr, having low toxicity, being non-carcinogenic, and as a cationic dye, Methyl Green is resistant to photobleaching. This study aims to determine the optimal concentration and staining duration of Methyl Green as a DNA dye for examining Escherichia coli DNA bands using agarose gel electrophoresis. Method: The research method used is experimental. Amplified Escherichia coli 16S rRNA gene DNA, sized 584 bp, which has undergone electrophoresis, was stained with Methyl Green dye at concentrations of 0.10%, 0.15%, 0.20%, 0.25%, 0.00015%, 0.00020%, 0.00025%, and 0.00030% with varying immersion times of 10, 15, 20, and 25 minutes. Result: The resulting DNA bands were analyzed or measured for surface area using ImageJ software. The mean value for each experimental group was calculated. The highest mean value was used as the basis for determining the most optimal condition. Conclusion: This study concludes that the optimal concentration and staining duration of Methyl Green, based on the highest mean value of 19,844,845, is 0.00030% Methyl Green with a staining duration of 25 minutes.